“You Don’t Have a Leg? Don’t Worry, You Can Still Be a Star!” Media Image of Cyclist Jiří Ježek - Veronika Macková; Ondřej Trunečka (Communication Today, 2025)
The article provides a theoretical and analytical insight into the framework of celebritization in sports; it mainly deals with the world of athletes with physical disabilities. The authors focus on the media image of Jiří Ježek, the most successful cyclist in the history of Paralympic Games, created by Czech public television, Česká televize, and Czech private television, TV Nova. The content analyses of their main sports broadcasts (TV sports news) were the most important research item. The quantitative research (how often he has been presented by TV stations in question during the last fourteen years) was followed by the qualitative research methods (how they have presented him and his story). The authors also contacted the companies to find out why they chose him as a figure to present themselves. Using the research findings as well as other sources of information, the article presents the media image of Jiří Ježek and outlines in detail the process of celebritization of an athlete with a disability who has become really famous, a real star.